Safety of autologous freshly expanded mesenchymal stromal cells for the treatment of graft-versus-host disease - Stenger, Elizabeth; Giver, Cynthia R.; Langston, Amelia; Kota, Daniel; Das, Pankoj Kumar; Chinnadurai, Raghavan; Galipeau, Jacques; Waller, Edmund K.; Qayed, Muna (Frontiers in Immunology, 2022)
Despite the curative potential of hematopoietic cell transplantation (HCT) for hematologic malignancies, graft-versus-host disease (GVHD) remains a substantial cause of morbidity and mortality, particularly if treatment refractory. Treatment with additional immunosuppression including steroids often lead to opportunistic infections and organ dysfunction. Novel therapies are greatly needed, specifically ones that lead to responses in treatment refractory patients and are better tolerated. Mesenchymal stromal cells (MSCs) are non-hematopoietic tolerogenic cells present in normal bone marrow (BM) which can be expanded ex vivo to therapeutic doses. Their safety and efficacy have been assessed in inflammatory disorders including GVHD, but heterogeneity in clinical responses has led some to examine MSC manufacturing and administration procedures which may impact in vivo efficacy. We hypothesized that autologous, early passage, and culture-recovered (post freeze and thaw) MSCs would be safe and may have superior efficacy. In this phase I single center trial, we assessed MSC safety and early efficacy of escalating number of doses (2x106/kg doses; dose level 1 – single dose; dose level 2 – two weekly doses; dose level 3 – four weekly doses) in patients >/=12 years with treatment refractory acute or chronic GVHD. Eleven enrolled patients received some or all planned MSC infusions, with median age at enrollment of 37 years. Most common primary HCT indication was leukemia, and median time from HCT to 1st MSC infusion was 2.6 years. MSC infusion was well tolerated, with all severe adverse events expected and determined to be unlikely or definitely not related to study. Thus, no dose limiting toxicities occurred the 3 dose levels. Three of 4 patients with acute GVHD (or overlap with acute features) had response seen at any time point, ranging from partial to complete. In those with a chronic GVHD indication (n=7), overall response at 3 months was partial in 5, stable in 1, and progressive in 1. No appreciable differences were seen between doses levels in peripheral blood lymphocyte subsets. In conclusion, autologous and culture recovered MSCs were safe in the setting of refractory GVHD following HCT for hematologic malignancy, and clinical responses were most notable in patients with acute GVHD.